Glyphosate and nutrient retention in preferential flow pathways - Giaccio, Gustavo Carlos María; Laterra, Pedro; Aparicio, Virginia Carolina; Costa, Jose Luis; Puricelli, Marino Marcelo (Asociación Argentina de Ecología, 2019)
Riparian vegetation strips (RVS) reduce surface runoff volume and retain sediments, pesticides and nutrients that are transported across them from adjacent crop-fields (CF). The ability of these strips to retain glyphosate has been demonstrated using experimental plots, but the spatial variability of that process is unknown. In this work, the influence of microtopography inside the RVS on the retention of glyphosate (and its major metabolite, AMPA), phosphorus and nitrogen were analyzed within a RVS of agricultural landscapes. Retention levels inside and outside preferential flow pathways (PFP) were compared under presence and absence of a tree stratum. Soil glyphosate + AMPA concentration within PFP was 88-fold higher than outside. Phosphorus and nitrogen soil concentrations, clay and bulk density were also higher inside than outside the PFP. The tree stratum did not modify soil concentration of glyphosate + AMPA, phosphorus, nitrogen, clay content, nor the morphometry of the PFP. Bulk density and clay content recorded in adjacent CF and in PFP, in addition to the high glyphosate, phosphorus and nitrogen concentrations in PFP soil, are consistent with a hydraulic connection between the CF and the PFP. These results contrast with some conclusions obtained from experimental studies under uniform plots and emphasize the importance of taking into account the genesis and structure of PFP in the design, evaluation and management of the filtering function of RVS.